The heterogeneity of megakaryocytes and platelets and implications for ex vivo platelet generation - Cuicui Liu (Wiley, 2021)
Abstract Platelets, the chief effector of hemostasis, are small anucleate blood cells generated from megakaryocytes (MKs), and the defects in platelet production or function lead to a variety of bleeding complications. Emerging evidence indicates that MKs and platelets are much more diverse than previously appreciated and involved in many physiological and pathological processes besides hemostasis, such as innate and adaptive immune responses, angiogenesis, and tumor metastasis, while the ontogenic variations in MK and platelet function have also become a focus in the field. However, whether MKs and platelets fulfill these distinct functions by utilizing distinct subpopulations remains poorly understood. New studies aimed at deciphering the MK transcriptome at the single‐cell level have provided some key insights into the functional heterogeneity of MKs. In this review, we will discuss some of the recent discoveries of functional and developmental heterogeneity of MKs and its potential link to the heterogeneity of platelets. We will also discuss the implications of these findings while focusing on the ex vivo generation of platelets from human pluripotent stem cells. The improved understanding of the heterogeneity underlying human MK development and platelet production should open new avenues for future platelet regeneration and clinical treatment of related diseases.